Intravitreal short-hairpin RNA attenuated adeno-associated virus-induced knockdown of amphiregulin and axial elongation in experimental myopia - Dong, Li; Zhang, Rui-Heng; Wu, Hao-Tian; Li, He-Yan; Zhou, Wen-Da; Shi, Xu-Han; Yu, Chu-Yao; Li, Yi-Tong; Li, Yi-Fan; Jonas, Jost B.; Wei, Wen-Bin (Investigative ophthalmology & visual science, 2023)
Epidermal growth factor (EGF) and its family members have been reported to be involved in myopic axial elongation. We examined whether short hairpin RNA attenuated adeno-associated virus (shRNA-AAV)-induced knockdown of amphiregulin, an EGF family member, has an influence on axial elongation. Three-week-old pigmented guinea pigs underwent lens-induced myopization (LIM) without additional intervention (LIM group; n = 10 animals) or additionally received into their right eyes at baseline an intravitreal injection of scramble shRNA-AAV (5 × 1010 vector genome [vg]) (LIM + Scr-shRNA group; n = 10) or of amphiregulin (AR)-shRNA-AAV (5 × 1010 vg/5 µL) (LIM + AR-shRNA-AAV group; n = 10), or they received an injection of AR-shRNA-AAV at baseline and three weekly amphiregulin injections (20 ng/5 µL) (LIM + AR-shRNA-AAV + AR group; n = 10). The left eyes received equivalent intravitreal injections of phosphate-buffered saline. Four weeks after baseline, the animals were sacrificed. At study end, interocular axial length difference was higher (P < 0.001), choroid and retina were thicker (P < 0.05), and relative expression of amphiregulin and p-PI3K, p-p70S6K, and p-ERK1/2 was lower (P < 0.05) in the LIM + AR-shRNA-AAV group than in any other group. The other groups did not differ significantly when compared with each other. In the LIM + AR-shRNA-AAV group, the interocular axial length difference increased with longer study duration. TUNEL assay did not reveal significant differences among all groups in retinal apoptotic cell density. In vitro retinal pigment epithelium cell proliferation and migration were the lowest (P < 0.05) in the LIM + AR-shRNA-AAV group, followed by the LIM + AR-shRNA-AAV + AR group. shRNA-AAV-induced knockdown of amphiregulin expression, in association with suppression of epidermal growth factor receptor signaling, attenuated axial elongation in guinea pigs with LIM. The finding supports the notion of EGF playing a role in axial elongation.